Impact of large-scale oceanic variability on Adriatic fisheries evidenced through the ‘mean temperature of the catch’ approach - Kamberi, Elvis; Hala, Edmond; Möllmann, Christian (Frontiers in Marine Science, 2025)
Climate change is significantly impacting marine ecosystems, altering their structure and functioning by influencing all levels of organization. The effects of global warming alter the productivity of marine fish populations and cause shifts in their geographical distribution towards higher latitudes, altogether affecting resource availability for fisheries. The mean temperature of the catch (MTC) is an index used to assess the effect of climate warming on fisheries. MTC is calculated based on the preferred temperature of exploited species, weighted by their annual catch. In our study, we calculated the MTC for Adriatic Sea fishery landings over five decades (1970-2020) to evaluate the response of the local fish community to warming. Our results show that after an initial decreasing trend until the late 1980s at a rate of 0.48°C per decade, the MTC subsequently increased at a rate of 0.24°C per decade. The MTC trend correlated significantly with regional climate indices, such as the North Atlantic Oscillation (NAO) and the Atlantic Multidecadal Oscillation (AMO). Adriatic landings exhibit distinct temporal shifts in the ratio of warm-water to cold-water species, contrasting with patterns observed in other Mediterranean regions. Nevertheless, despite these fluctuations, the contribution of various warm-water species has increased over the last 15 years. Although this study suggests a lower increasing rate in the MTC in recent decades compared to other Mediterranean areas, it highlights that the Adriatic fish community is experiencing significant changes in relation to sea warming and demonstrates the MTC to be a useful indicator for changes in the Adriatic fish community composition.